Rewarming the Primordial Soup: Revisitations and Rediscoveries in Prebiotic Chemistry - Saladino, Raffaele; Šponer, Judit E; Šponer, Jiří; Di Mauro, Ernesto (Chembiochem, 2018)
A short history of Campbell's primordial soup: In this essay we try to disclose some of the historical connections between the studies that have contributed to our current understanding of the emergence of catalytic RNA molecules and their components from an inanimate matter.
Keywords: nucleotides; nucleosides; Ribosomes; Prebiotics; oligonucleotides; prebiotika; RNA; RNA, Catalytic; prebiotic chemistry; nukleotidy; Nucleosides; RNA katalytická; nukleosidy; ribozomy; Nucleotides